A Bohmian trajectory analysis of singular wave functions - Sanz, Ángel S.; Sanchez-Soto, Luis L.; Aiello, Andrea (Physics Letters A, 2024)
The Schrödinger equation admits smooth and finite solutions that spontaneously evolve into a singularity, even for a free particle. This blowup is generally ascribed to the intrinsic dispersive character of the associated time evolution. We resort to the notion of quantum Bohmian trajectories to relate this singular behavior to local phase variations, which generate an underlying velocity field responsible for driving the quantum flux toward the singular region.<br
Keywords: Bohmian mechanics; Singularities; Quantum flow; Self-focusing

A non-separability measure for spatially disjoint vectorial fields - Aiello, Andrea; Hu, Xiao-Bo; Rodriguez-Fajardo, Valeria; Forbes, Andrew; Hernandez-Aranda, Raul; Perez-Garcia, Benjamin; Rosales-Guzman, Carmelo (New Journal of Physics, 2022)
Vectorial forms of structured light that are non-separable in their spatial and polarisation degrees of freedom have become topical of late, with an extensive toolkit for their creation and control. In contrast, the toolkit for quantifying their non-separability, the inhomogeneity of the polarisation structure, is less developed and in some cases fails altogether. To overcome this, here we introduce a new measure for vectorial light, which we demonstrate both theoretically and experimentally. We consider the general case where the local polarisation homogeneity can vary spatially across the field, from scalar to vector, a condition that can arise naturally if the composite scalar fields are path separable during propagation, leading to spatially disjoint vectorial light. We show how the new measure correctly accounts for the local path-like separability of the individual scalar beams, which can have varying degrees of disjointness, even though the global vectorial field remains intact. Our work attempts to address a pressing issue in the analysis of such complex light fields, and raises important questions on spatial coherence in the context of vectorially polarised light.
Created from Fastlane, WoS look-up

A versatile source of single photons for quantum information processing - Förtsch, Michael; Fürst, Josef; Wittmann, Christoffer; Strekalov, Dmitry; Aiello, Andrea; Chekhova, Maria V.; Leuchs, Gerd; Silberhorn, Christine; Marquardt, Christoph (Nature Communications, 2013)
The generation of high-quality single-photon states with controllable narrow spectral bandwidths and central frequencies is key to facilitate efficient coupling of any atomic system to non-classical light fields. Such an interaction is essential in numerous experiments for fundamental science and applications in quantum communication and information processing, as well as in quantum metrology. Here we implement a fully tunable, narrow-band and efficient single-photon source based on a whispering gallery mode resonator. Our disk-shaped, monolithic and intrinsically stable resonator is made of lithium niobate and supports a cavity-assisted spontaneous parametric down-conversion process. The generated photon pairs are emitted into two highly tunable resonator modes. We verify wavelength tuning over 100 nm of both modes with controllable bandwidth between 7.2 and 13 MHz. Heralding of single photons yields anti-bunching with g (2) (0)<0.2. © 2013 Macmillan Publishers Limited. All rights reserved.
CRIS-Team Scopus Importer:2022-06-05

Cavity optomechanics in a levitated helium drop - Childress, Lilian; Schmidt, M. P.; Kashkanova, A. D.; Brown, C. D.; Harris, G. I.; Aiello, Andrea; Marquardt, Florian; Harris, J. G. E. (Physical Review A, 2017)
We describe a proposal for a type of optomechanical system based on a drop of liquid helium that is magnetically levitated in vacuum. In the proposed device, the drop would serve three roles: its optical whispering-gallery modes would provide the optical cavity, its surface vibrations would constitute the mechanical element, and evaporation of He atoms from its surface would provide continuous refrigeration. We analyze the feasibility of such a system in light of previous experimental demonstrations of its essential components: magnetic levitation of mm-scale and cm-scale drops of liquid He, evaporative cooling of He droplets in vacuum, and coupling to high-quality optical whispering-gallery modes in a wide range of liquids. We find that the combination of these features could result in a device that approaches the single-photon strong-coupling regime, due to the high optical quality factors attainable at low temperatures. Moreover, the system offers a unique opportunity to use optical techniques to study the motion of a superfluid that is freely levitating in vacuum (in the case of He4). Alternatively, for a normal fluid drop of He3, we propose to exploit the coupling between the drop's rotations and vibrations to perform quantum nondemolition measurements of angular momentum.
CRIS-Team Scopus Importer:2023-03-27

Classical and quantum properties of cylindrically polarized states of light - Holleczek, Annemarie; Aiello, Andrea; Gabriel, Christian; Marquardt, Christoph; Leuchs, Gerd (Optics Express, 2011)
We investigate theoretical properties of beams of light with non-uniform polarization patterns. Specifically, we determine all possible configurations of cylindrically polarized modes (CPMs) of the electromagnetic field, calculate their total angular momentum and highlight the subtleties of their structure. Furthermore, a hybrid spatio-polarization description for such modes is introduced and developed. In particular, two independent Poincaré spheres have been introduced to represent simultaneously the polarization and spatial degree of freedom of CPMs. Possible mode-to-mode transformations accomplishable with the help of Bconventional polarization and spatial phase retarders are shown within this representation. Moreover, the importance of these CPMs in the quantum optics domain due to their classical features is highlighted. © 2011 Optical Society of America.
CRIS-Team Scopus Importer:2022-06-05

Classical entanglement in polarization metrology - Toeppel, Falk; Aiello, Andrea; Marquardt, Christoph; Giacobino, Elisabeth; Leuchs, Gerd (New Journal of Physics, 2014)
Quantum approaches relying on entangled photons have been recently proposed to increase the efficiency of optical measurements. We demonstrate here that, surprisingly, the use of classical light with entangled degrees of freedom can also bring outstanding advantages over conventional measurements in polarization metrology. Specifically, we show that radially polarized beams of light allow to perform real-time single-shot Mueller matrix polarimetry. Our results also indicate that quantum optical procedures requiring entanglement without nonlocality can be actually achieved in the classical optics regime. © 2014 IOP Publishing Ltd and Deutsche Physikalische Gesellschaft.
CRIS-Team Scopus Importer:2022-06-05
Keywords: applied classical electromagnetism; entanglement and quantum nonlocality; polarization

Classically entangled optical beams for high-speed kinematic sensing - Berg-Johansen, Stefan; Töppel, Falk; Stiller, Birgit; Banzer, Peter; Ornigotti, Marco; Giacobino, Elisabeth; Leuchs, Gerd; Aiello, Andrea; Marquardt, Christoph (Optica, 2015)
Tracking the kinematics of fast-moving objects is an important diagnostic tool for science and engineering. Here, we demonstrate an approach to positional and directional sensing based on the concept of classical entanglement in vector beams of light [Found. Phys. 28, 361–374 (1998)]. The measurement principle relies on the intrinsic correlations existing in such beams between transverse spatial modes and polarization. The latter can be determined from intensity measurements with only a few fast photodiodes, greatly outperforming the bandwidth of current CCD/CMOS devices. In this way, our setup enables two-dimensional real-time sensing with temporal resolution in the GHz range. We expect the concept to open up new directions in metrology and sensing.
CRIS-Team Scopus Importer:2021-06-29
Keywords: Classical and quantum physics; Optical sensing and sensors

Cluster state generation with quadrature squeezed cylindrically polarized modes - Gabriel, Christian; Rigas, Ioannes; Aiello, Andrea; Berg-Johansen, Stefan; van Loock, Peter; Marquardt, Christoph; Leuchs, Gerd (2012 Conference on Lasers and Electro-Optics, CLEO 2012, 2012)
We present schemes which exploit the hybrid-entanglement in quadrature squeezed cylindrically polarized modes to generate cluster states. Such states are essential for one-way quantum computing. © 2012 OSA.
CRIS-Team Scopus Importer:2022-06-05

Continuously adjustable narrow-band heralded single photon source - Förtsch, Michael; Fürst, Josef; Wittmann, Christoffer; Strekalov, Dmitry; Aiello, Andrea; Silberhorn, Christine; Marquardt, Christoph; Leuchs, Gerd (2012 Conference on Lasers and Electro-Optics, CLEO 2012, 2012)
We present the high efficient generation of narrow-band heralded single photons, widely tunable in wavelength and bandwidth using resonator enhanced spontaneous down conversion in a crystalline whispering gallery mode resonator. © 2012 OSA.
CRIS-Team Scopus Importer:2022-06-05

Demonstration of a state of light with purely transverse angular momentum - Banzer, Peter; Neugebauer, Martin; Aiello, Andrea; Marquardt, Christoph; Lindlein, Norbert; Bauer, Thomas; Leuchs, Gerd (Optics InfoBase Conference Papers, 2013)
We demonstrate and discuss a state of light with purely transverse angular momentum - a photonic wheel - generated by tight focusing of polarization tailored light. We use an experimental nanoprobing technique to measure the corresponding distribution.
CRIS-Team Scopus Importer:2022-06-05

Demonstration of local teleportation using classical entanglement - Guzman-Silva, Diego; Bruening, Robert; Zimmermann, Felix; Vetter, Christian; Graefe, Markus; Heinrich, Matthias; Nolte, Stefan; Duparre, Michael; Aiello, Andrea; Ornigotti, Marco; Szameit, Alexander (2017 Conference on Lasers and Electro-Optics, CLEO 2017 - Proceedings, 2017)
We report on an optical implementation of the teleportation protocol in the classical realm, solely based on entanglement between spatial and modal degrees of freedom of a purely classical light field.
CRIS-Team Scopus Importer:2023-04-20

Detecting the spatial quantum uncertainty of bosonic systems - Chille, Vanessa; Treps, Nicolas; Fabre, Claude; Leuchs, Gerd; Marquardt, Christoph; Aiello, Andrea (New Journal of Physics, 2016)
We present the quantum theory of direct detection of bosonic particles by multipixel detectors. For the sake of clarity, we specialize on beams of photons, and we study the measurement of different spatial beam characteristics, as position and width. The limits of these measurements are set by the quantum nature of the light field. We investigate how both, detector imperfections and finite pixel size affect the photon counting distribution. An analytic theory for the discretized detection setup is derived. We discuss the results and compare them to the theory presented by Chille et al 2015 Opt. Express 23 32777, which investigates the beam width noise independently of the measurement system. Finally, we present numerical simulations that furnish realistic and promising predictions for possible experimental studies.
CRIS-Team Scopus Importer:2022-06-05
Keywords: bosonic systems; quantum uncertainty; spatial measurements

Direct measurement of the geometric spin hall effect of light - Korger, Jan; Aiello, Andrea; Chille, Vanessa; Wittmann, Christoffer; Banzer, Peter; Lindlein, Norbert; Marquardt, Christoph; Leuchs, Gerd (Frontiers in Optics, FIO 2012, 2012)
We experimentally demonstrate a recently predicted novel beam shift phenomenon, the geometric spin Hall effect of light. This effect is fundamentally different from ordinary beam shifts due to its purely geometric nature. © OSA 201

Entangling different degrees of freedom by quadrature squeezing cylindrically polarized modes - Gabriel, C.; Aiello, Andrea; Zhong, W.; Euser, T. G.; Joly, N. Y.; Banzer, Peter; Foertsch, M.; Elser, Dominique; Andersen, U. L.; Marquardt, Christoph; Russell, P. St. J.; Leuchs, Gerd (Physical Review Letters, 2011)
Quantum systems such as, for example, photons, atoms, or Bose-Einstein condensates, prepared in complex states where entanglement between distinct degrees of freedom is present, may display several intriguing features. In this Letter we introduce the concept of such complex quantum states for intense beams of light by exploiting the properties of cylindrically polarized modes. We show that already in a classical picture the spatial and polarization field variables of these modes cannot be factorized. Theoretically it is proven that by quadrature squeezing cylindrically polarized modes one generates entanglement between these two different degrees of freedom. Experimentally we demonstrate amplitude squeezing of an azimuthally polarized mode by exploiting the nonlinear Kerr effect in a specially tailored photonic crystal fiber. These results display that such novel continuous-variable entangled systems can, in principle, be realized.© 2011 American Physical Society.
CRIS-Team Scopus Importer:2022-06-05

Experimental demonstration of the geometric spin hall effect of light in highly focused vector beams - Neugebauer, Martin; Banzer, Peter; Bauer, Thomas; Lindlein, Norbert; Aiello, Andrea; Marquardt, Christoph; Korger, Jan; Leuchs, Gerd (Quantum Electronics and Laser Science Conference, QELS 2012, 2012)
We demonstrate the geometric spin Hall effect of light by focusing a specially polarization tailored beam of light, resulting in the generation of purely transverse angular momentum in the focal plane. © 2012 OS

Experimental generation of amplitude squeezed vector beams - Chille, Vanessa; Berg-Johansen, Stefan; Semmler, Marion; Banzer, Peter; Aiello, Andrea; Leuchs, Gerd; Marquardt, Christoph (Optics Express, 2016)
We present an experimental method for the generation of amplitude squeezed high-order vector beams. The light is modified twice by a spatial light modulator such that the vector beam is created by means of a collinear interferometric technique. A major advantage of this approach is that it avoids systematic losses, which are detrimental as they cause decoherence in continuous-variable quantum systems. The utilisation of a spatial light modulator (SLM) gives the flexibility to switch between arbitrary mode orders. The conversion efficiency with our setup is only limited by the efficiency of the SLM. We show the experimental generation of Laguerre-Gauss (LG) modes with radial indices 0 or 1 and azimuthal indices up to 3 with complex polarization structures and a quantum noise reduction up to -0.9dB±0.1dB. The corresponding polarization structures are studied in detail by measuring the spatial distribution of the Stokes parameters.
CRIS-Team Scopus Importer:2022-06-05

Geometric Spin Hall Effect of Light at polarizing interfaces - Korger, J.; Aiello, Andrea; Gabriel, C.; Banzer, Peter; Kolb, T.; Marquardt, Christoph; Leuchs, Gerd (Applied Physics B-Lasers and Optics, 2011)
The geometric Spin Hall Effect of Light (geometric SHEL) amounts to a polarization-dependent positional shift when a light beam is observed from a reference frame tilted with respect to its direction of propagation. Motivated by this intriguing phenomenon, the energy density of the light beam is decomposed into its Cartesian components in the tilted reference frame. This illustrates the occurrence of the characteristic shift and the significance of the effective response function of the detector. We introduce the concept of a tilted polarizing interface and provide a scheme for its experimental implementation. A light beam passing through such an interface undergoes a shift resembling the original geometric SHEL in a tilted reference frame. This displacement is generated at the polarizer and its occurrence does not depend on the properties of the detection system.We give explicit results for this novel type of geometric SHEL and show that at grazing incidence this effect amounts to a displacement of multiple wavelengths, a shift larger than the one introduced by Goos-Hänchen and Imbert-Fedorov effects. © 2011 Springer-Verlag.
CRIS-Team Scopus Importer:2022-06-05

Geometric spin Hall effect of light in tightly focused polarization-tailored light beams - Neugebauer, Martin; Banzer, Peter; Bauer, Thomas; Orlovas, Sergejus; Lindlein, Norbert; Aiello, Andrea; Leuchs, Gerd (Physical Review A - Atomic, Molecular, and Optical Physics, 2014)

GHz kinematic sensing with classically entangled beams of light - Berg-Johansen, Stefan; Töppel, Falk; Stiller, Birgit; Banzer, Peter; Ornigotti, M.; Giacobino, E.; Leuchs, Gerd; Aiello, Andrea; Marquardt, Christoph (Optics InfoBase Conference Papers, 2015)
CRIS-Team Scopus Importer:2021-06-29

Helicity, chirality, and spin of optical fields without vector potentials - Aiello, Andrea (Physical Review A, 2022)
Helicity H, chirality C, and spin angular momentum S are three physical observables that play an important role in the study of optical fields. These quantities are closely related, but their connection is hidden by the use of four different vector fields for their representation, namely, the electric and magnetic fields E and B, and the two transverse potential vectors C and A. Helmholtz's decomposition theorem restricted to solenoidal vector fields entails the introduction of a bona fide inverse curl operator, which permits one to express the above three quantities in terms of the observable electric and magnetic fields only. This yields clear expressions for H,C, and S, which are automatically gauge invariant and display electric-magnetic democracy.
Created from Fastlane, Scopus look-up

Indistinguishable MHz-narrow heralded photon pairs from a whispering gallery resonator - Huang, Sheng-Hsuan; Dirmeier, Thomas; Shafiee, Golnoush; Laiho, Kaisa; Strekalov, Dmitry V.; Aiello, Andrea; Leuchs, Gerd; Marquardt, Christoph (APL Photonics, 2025)
The Hong-Ou-Mandel interference plays a vital role in many quantum optical applications where indistinguishability of two photons is important. Such photon pairs are commonly generated as the signal and idler in the polarization-degenerate spontaneous parametric downconversion (SPDC). To scale this approach to a larger number of photons, we demonstrate how two independent signal photons radiated into different spatial modes can be rendered conditionally indistinguishable by a heralding measurement performed on their respective idlers. We use the SPDC in a whispering gallery resonator, which is already proven to be versatile sources of quantum states. Its extreme conversion efficiency allowed us to perform our measurements with only 50 nW of in-coupled pump power in each propagation direction. The Hong-Ou-Mandel interference of two counterpropagating signal photons manifested itself in the fourfold coincidence rate, where the detection of two idler photons heralds a pair of signal photons with a desired temporal overlap. We achieved the Hong-Ou-Mandel dip contrast of 74% ± 5%. Importantly, the optical bandwidth of all involved photons is of the order of a MHz and is continuously tunable. This, on the one hand, makes it possible to achieve the necessary temporal measurement resolution with standard electronics and, on the other hand, creates a quantum state source compatible with other candidates for qubit implementation, such as optical transitions in solid-state or vaporous systems. We also discuss the possibility of generating photon pairs with similar temporal modes from two different whispering gallery resonators.
CRIS-Team Scopus Importer:2025-05-30

Low-threshold optical parametric oscillations in a whispering gallery mode resonator - Fuerst, J. U.; Strekalov, D. V.; Elser, Dominique Alexander; Aiello, Andrea; Andersen, U. L.; Marquardt, Christoph; Leuchs, Gerd (Physical Review Letters, 2010)
In whispering gallery mode (WGM) resonator light is guided by continuous total internal reflection along a curved surface. Fabricating such resonators from an optically nonlinear material one takes advantage of their exceptionally high quality factors and small mode volumes to achieve extremely efficient optical frequency conversion. Our analysis of the phase-matching conditions for optical parametric down-conversion (PDC) in a spherical WGM resonator shows their direct relation to the sum rules for photons' angular momenta and predicts a very low parametric oscillation threshold. We realized such an optical parametric oscillator (OPO) based on naturally phase-matched PDC in lithium niobate. We demonstrated a single-mode, strongly nondegenerate OPO with a threshold of 6.7μW and linewidth under 10 MHz. This work demonstrates the remarkable capabilities of WGM-based OPOs. © 2010 The American Physical Society.
CRIS-Team Scopus Importer:2022-06-05

Metasurface-Based Hybrid Optical Cavities for Chiral Sensing - Baßler, Nico; Aiello, Andrea; Schmidt, Kai Phillip; Genes, Claudiu; Reitz, Michael (Physical Review Letters, 2024)
Quantum metasurfaces, i.e., two-dimensional subwavelength arrays of quantum emitters, can be employed as mirrors towards the design of hybrid cavities, where the optical response is given by the interplay of a cavity-confined field and the surface modes supported by the arrays. We show that stacked layers of quantum metasurfaces with orthogonal dipole orientation can serve as helicity-preserving cavities. These structures exhibit ultranarrow resonances and can enhance the intensity of the incoming field by orders of magnitude, while simultaneously preserving the handedness of the field circulating inside the resonator, as opposed to conventional cavities. The rapid phase shift in the cavity transmission around the resonance can be exploited for the sensitive detection of chiral scatterers passing through the cavity. We discuss possible applications of these resonators as sensors for the discrimination of chiral molecules. Our approach describes a new way of chiral sensing via the measurement of particle-induced phase shifts.
CRIS-Team Scopus Importer:2024-02-09

Microsphere kinematics from the polarization of tightly focused nonseparable light - Berg-Johansen, Stefan; Neugebauer, Martin; Aiello, Andrea; Leuchs, Gerd; Banzer, Peter; Marquardt, Christoph (Optics Express, 2021)
Recently, it was shown that vector beams can be utilized for fast kinematic sensing via measurements of their global polarization state [Optica 2, 864 (2015)]. The method relies on correlations between the spatial and polarization degrees of freedom of the illuminating field which result from its nonseparable mode structure. Here, we extend the method to the nonparaxial regime. We study experimentally and theoretically the far-field polarization state generated by the scattering of a dielectric microsphere in a tightly focused vector beam as a function of the particle position. Using polarization measurements only, we demonstrate position sensing of a Mie particle in three dimensions. Our work extends the concept of back focal plane interferometry and highlights the potential of polarization analysis in optical tweezers employing structured light.
CRIS-Team Scopus Importer:2021-04-30

Nonparaxial polarizers - Aiello, Andrea; Marquardt, Christoph; Leuchs, Gerd (Optics Letters, 2009)
We develop a theoretical description for polarizers that goes beyond the paraxial approximation. By combining existing theories for fields with nonplanar wavefronts, we are able to derive a simple power series expansion expressing the electric field of a light beam after a polarizer as a linear function of the field and its spatial derivatives evaluated before the polarizer. The first few terms of such expansion are explicitly given, and their physical meaning is discussed. © 2009 Optical Society of America.
CRIS-Team Scopus Importer:2022-06-05

Observation of the Geometric Spin Hall Effect of Light - Korger, Jan; Aiello, Andrea; Chille, Vanessa; Wittmann, Christoffer; Lindlein, Norbert; Marquardt, Christoph; Leuchs, Gerd (Physical Review Letters, 2014)

One more time on the helicity decomposition of spin and orbital optical currents - Aiello, Andrea (Journal of Physics A: Mathematical and Theoretical, 2022)
The helicity representation of the linear momentum density of a light wave is well understood for monochromatic optical fields in both paraxial and non-paraxial regimes of propagation. In this note we generalize such representation to nonmonochromatic optical fields. We find that, differently from the monochromatic case, the linear momentum density, aka the Poynting vector divided by c 2, does not separate into the sum of right-handed and left-handed terms, even when the so-called electric-magnetic democracy in enforced by averaging the electric and magnetic contributions. However, for quasimonochromatic light, such a separation is approximately restored after time-averaging. This paper is dedicated to Sir Michael Berry on the occasion of his 80th birthday.
Created from Fastlane, Scopus look-up
Keywords: helicity; non-monochromatic light; Poynting vector; spin and orbital angular momentum of light

Optical properties of a tilted polarizer and geometric spin hall effect of light - Korger, Jan; Aiello, Andrea; Gabriel, Christian; Banzer, Peter; Kolb, Tobias; Marquardt, Christoph; Leuchs, Gerd (Optics InfoBase Conference Papers, 2011)
CRIS-Team Scopus Importer:2022-06-05

Perturbation theory of nearly spherical dielectric optical resonators - Gohsrich, Julius; Shah, Tirth; Aiello, Andrea (Physical Review A, 2021)
Dielectric spheres of various sizes may sustain electromagnetic whispering-gallery modes resonating at optical frequencies with very narrow linewidths. Arbitrary small deviations from the spherical shape typically shift and broaden such resonances. Our goal is to determine these shifted and broadened resonances. A boundary-condition perturbation theory for the acoustic vibrations of nearly circular membranes was developed by Rayleigh more than a century ago. We extend this theory to describe the electromagnetic excitations of nearly spherical dielectric cavities. This approach permits us to avoid dealing with decaying quasinormal modes. We explicitly find the frequencies and the linewidths of the optical resonances for arbitrarily deformed nearly spherical dielectric cavities, as power series expansions by a small parameter, up to and including second-order terms. We thoroughly discuss the physical conditions for the applicability of perturbation theory.
CRIS-Team WoS Importer:2021-09-03

Perturbation theory of optical resonances of deformed dielectric spheres - Aiello, Andrea; Harris, Jack G. E.; Marquardt, Florian (Physical Review A, 2019)
We analyze the optical resonances of a dielectric sphere the surface of which has been slightly deformed in an arbitrary way. Setting up a perturbation series up to second order, we derive both the frequency shifts and the modified linewidths. Our theory is applicable, for example, to freely levitated liquid drops or solid spheres, which are deformed by thermal surface vibrations, centrifugal forces, or arbitrary surface waves. A dielectric sphere is effectively an open system the description of which requires the introduction of non-Hermitian operators characterized by complex eigenvalues and non-normalizable eigenfunctions. We avoid these difficulties using the Kapur-Peierls formalism, which enables us to extend the popular Rayleigh-Schrodinger perturbation theory to the case of electromagnetic Debye potentials describing the light fields inside and outside the near-spherical dielectric object. We find analytical formulas, valid within certain limits, for the deformation-induced first- and second-order corrections to the central frequency and bandwidth of a resonance. As an application of our method, we compare our results with preexisting ones, finding full agreement.
CRIS-Team WoS Importer:2019-09-10

Quantum Light from a Whispering-Gallery-Mode Disk Resonator - Fuerst, J. U.; Strekalov, D. V.; Elser, Dominique; Aiello, Andrea; Andersen, U. L.; Marquardt, Christoph; Leuchs, Gerd (Physical Review Letters, 2011)
Optical parametric down-conversion has proven to be a valuable source of nonclassical light. The process is inherently able to produce twin-beam correlations along with individual intensity squeezing of either parametric beam, when pumped far above threshold. Here, we present for the first time the direct observation of intensity squeezing of -1.2dB of each of the individual parametric beams in parametric down-conversion by use of a high quality whispering-gallery-mode disk resonator. In addition, we observed twin-beam quantum correlations of -2.7dB with this cavity. Such resonators feature strong optical confinement and offer tunable coupling to an external optical field. This work exemplifies the potential of crystalline whispering-gallery-mode resonators for the generation of quantum light. The simplicity of this device makes the application of quantum light in various fields highly feasible. © 2011 American Physical Society.
CRIS-Team Scopus Importer:2022-06-05

Quantum-like nonseparable structures in optical beams - Aiello, Andrea; Töppel, Falk; Marquardt, Christoph; Giacobino, Elisabeth; Leuchs, Gerd (New Journal of Physics, 2015)
When two or more degrees of freedom become coupled in a physical system, a number of observables of the latter cannot be represented by mathematical expressions separable with respect to the different degrees of freedom. In recent years it appeared clear that these expressions may display the same mathematical structures exhibited by multiparty entangled states in quantum mechanics. In this work, we investigate the occurrence of such structures in optical beams, a phenomenon that is often referred to as 'classical entanglement'. We present a unified theory for different kinds of light beams exhibiting classical entanglement and we indicate several possible extensions of the concept. Our results clarify and shed new light upon the physics underlying this intriguing aspect of classical optics.
CRIS-Team Scopus Importer:2022-06-05
Keywords: classical entanglement; non-separability; optical beams

Quantum uncertainty in the beam width for optical spatial modes - Chille, Vanessa; Aiello, Andrea; Banzer, Peter; Leuchs, Gerd; Marquardt, Christoph; Treps, Nicolas; Fabre, Claude (2016 Conference on Lasers and Electro-Optics, CLEO 2016, 2016)
We theoretically investigate the quantum uncertainty in the width of optical beams. Many optical applications such as imaging and beam focusing are limited by the quantum noise in spatial characteristics of light beams.
CRIS-Team Scopus Importer:2022-06-05

Quantum uncertainty in the beam width of spatial optical modes - Chille, Vanessa; Banzer, Peter; Aiello, Andrea; Leuchs, Gerd; Marquardt, Christoph; Treps, Nicolas; Fabre, Claude (Optics Express, 2015)
We theoretically investigate the quantum uncertainty in the beam width of transverse optical modes and, for this purpose, define a corresponding quantum operator. Single mode states are studied as well as multimode states with small quantum noise. General relations are derived, and specific examples of different modes and quantum states are examined. For the multimode case, we show that the quantum uncertainty in the beam width can be completely attributed to the amplitude quadrature uncertainty of one specific mode, which is uniquely determined by the field under investigation. This discovery provides us with a strategy for the reduction of the beam width noise by an appropriate choice of the quantum state.
CRIS-Team Scopus Importer:2022-06-05

Renormalized Mutual Information for Artificial Scientific Discovery - Sarra, Leopoldo; Marquardt, Florian; Aiello, Andrea (Physical Review Letters, 2021)
We derive a well-defined renormalized version of mutual information that allows us to estimate the dependence between continuous random variables in the important case when one is deterministically dependent on the other. This is the situation relevant for feature extraction, where the goal is to produce a low-dimensional effective description of a high-dimensional system. Our approach enables the discovery of collective variables in physical systems, thus adding to the toolbox of artificial scientific discovery, while also aiding the analysis of information flow in artificial neural networks.
CRIS-Team Scopus Importer:2021-06-04

Self-healing of Bessel beams - Lindlein, Norbert; Merklein, Bastian; Aiello, Andrea (2016)

Single-mode squeezing in arbitrary spatial modes - Semmler, Marion; Berg-Johansen, Stefan; Chille, Vanessa; Gabriel, Christian; Banzer, Peter; Aiello, Andrea; Marquardt, Christoph; Leuchs, Gerd (Optics Express, 2016)
As the generation of squeezed states of light has become a standard technique in laboratories, attention is increasingly directed towards adapting the optical parameters of squeezed beams to the specific requirements of individual applications. It is known that imaging, metrology, and quantum information may benefit from using squeezed light with a tailored transverse spatial mode. However, experiments have so far been limited to generating only a few squeezed spatial modes within a given setup. Here, we present the generation of single-mode squeezing in Laguerre-Gauss and Bessel-Gauss modes, as well as an arbitrary intensity pattern, all from a single setup using a spatial light modulator (SLM). The degree of squeezing obtained is limited mainly by the initial squeezing and diffractive losses introduced by the SLM, while no excess noise from the SLM is detectable at the measured sideband. The experiment illustrates the single-mode concept in quantum optics and demonstrates the viability of current SLMs as flexible tools for the spatial reshaping of squeezed light.
CRIS-Team Scopus Importer:2022-06-05

The photonic wheel - demonstration of a state of light with purely transverse angular momentum - Banzer, Peter; Neugebauer, Martin; Aiello, Andrea; Marquardt, Christoph; Lindlein, Norbert; Bauer, Thomas; Leuchs, Gerd (Journal of the European Optical Society: Rapid Publications, 2013)

The polarization properties of a tilted polarizer - Korger, Jan; Kolb, Tobias; Banzer, Peter; Aiello, Andrea; Wittmann, Christoffer; Marquardt, Christoph; Leuchs, Gerd (Optics Express, 2013)
Polarizers are key components in optical science and technology. Thus, understanding the action of a polarizer beyond oversimplifying approximations is crucial. In this work, we study the interaction of a polarizing interface with an obliquely incident wave experimentally. To this end, a set of Mueller matrices is acquired employing a novel procedure robust against experimental imperfections. We connect our observation to a geometric model, useful to predict the effect of polarizers on complex light fields. © 2013 Optical Society of America.
CRIS-Team Scopus Importer:2022-06-05

Tools for detecting entanglement between different degrees of freedom in quadrature squeezed cylindrically polarized modes - Gabriel, C.; Aiello, Andrea; Berg-Johansen, S.; Marquardt, Christoph; Leuchs, Gerd (European Physical Journal D, 2012)
Quadrature squeezed cylindrically polarized modes contain entanglement not only in the polarization and spatial electric field variables but also between these two degrees of freedom [C. Gabriel et al., Phys. Rev. Lett. 106, 060502 (2011)]. In this paper we present tools to generate and detect this entanglement. Experimentally we demonstrate the generation of quadrature squeezing in cylindrically polarized modes by mode transforming a squeezed Gaussian mode. Specifically, -1.2dB ± 0.1 dB of amplitude squeezing are achieved in the radially and azimuthally polarized mode. Furthermore, theoretically it is shown how the entanglement contained within these modes can be measured and how strong the quantum correlations are, depending on the measurement scheme. © EDP Sciences, Società Italiana di Fisica, Springer-Verlag 2012.
CRIS-Team Scopus Importer:2022-06-05

Transverse Angular Momentum and Geometric Spin Hall Effect of Light - Aiello, Andrea; Lindlein, Norbert; Marquardt, Christoph; Leuchs, Gerd (Physical Review Letters, 2009)
We present a novel fundamental phenomenon occurring when a polarized beam of light is observed from a reference frame tilted with respect to the direction of propagation of the beam. This effect has a purely geometric nature and amounts to a polarization-dependent shift or split of the beam intensity distribution evaluated as the time-averaged flux of the Poynting vector across the plane of observation. We demonstrate that such a shift is unavoidable whenever the beam possesses a nonzero transverse angular momentum. This latter result has general validity and applies to arbitrary systems such as, e.g., electronic and atomic beams. © 2009 The American Physical Societ
UnivIS-Import:2015-03-09:Pub.2009.nat.dphy.optik.1optik.transv

Transverse angular momentum of photons - Aiello, Andrea; Marquardt, Christoph; Leuchs, Gerd (Physical Review A - Atomic, Molecular, and Optical Physics, 2010)
We develop the quantum theory of transverse angular momentum of light beams. The theory applies to paraxial and quasiparaxial photon beams in vacuum and reproduces the known results for classical beams when applied to coherent states of the field. Both the Poynting vector, alias the linear momentum, and the angular-momentum quantum operators of a light beam are calculated including contributions from first-order transverse derivatives. This permits a correct description of the energy flow in the beam and the natural emergence of both the spin and the angular momentum of the photons. We show that for collimated beams of light, orbital angular-momentum operators do not satisfy the standard commutation rules. Finally, we discuss the application of our theory to some concrete cases. © 2010 The American Physical Society.
CRIS-Team Scopus Importer:2022-06-05